Foreign trade act in transition - Mathias Lefeldt (Intereconomics, 1973)
“The flow of goods, services, capital, current payments and other transactions of trade across frontiers … is fundamentally free …” — with these words begins the German AuBenwirtschafts-Gesetz — AWG (Foreign Trade Act), Article Number One. After this Law had been passed in 1961, many interpreted its introduction as a sign that it represented a new Magna Charta of foreign trade.
Keywords: 330; Germany